Assessment of Postural Changes Among School-Going Children Due to Heavy Backpacks in Lahore - Jameel, Waleed; Batool, Sana; Ashraf, Hafiza Sana; Sohail, Maria; Manglani, Neha; Safdar, Zainab (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2021)
Posture is a matter a big concern. Because of increased workload the weight of school bags is also increasing day by day. The weight of bags with heavy books can develop many spinal deformities in young children. Objective: To assess the postural changes happening in school going kids because of heavy backpacks. Method: It is a cross sectional study and was conducted on different schools in Lahore, within the time period of three months from 1st November 2019 to 1st February 2020. The sample size was 145 and the survey followed convenient sampling technique. Children per inclusion criteria were selected from different government schools to collect data and informed consent was taken before data collection. REEDCO scale was used to examine the postural disturbance. Results: Results showed head posture as 3.4% poor & 13.1% fair, neck posture as 6.2% poor & 16.6% fair, shoulder posture as 5.5% poor & 15.2% fair, upper back posture as 3.4% poor & 38.6% fair, trunk posture as 10.3% poor & 46.2% fair, abdominal posture as 5.5% poor & 14.5% fair, hip posture as 0.7% poor & 5.5% fair and the ankle posture as 1.4% poor & 26.9% fair. Conclusion: This study concluded a significantly frequent postural problems in trunk region because of carrying heavy loaded school backpacks which is neither good in present time nor in future, as with the passage of time, postural changes become irreversible. Along with that, hip region prominently perceived least postural changes according to current study.